Finafloxacin, a Novel Fluoroquinolone, Reduces the Clinical Signs of Infection and Pathology in a Mouse Model of Q Fever - Hartley, M. Gill; Norville, Isobel H.; Richards, Mark I.; Barnes, Kay B.; Bewley, Kevin R.; Vipond, Julia; Rayner, Emma; Vente, Andreas; Armstrong, Stuart J.; Harding, Sarah V. (Frontiers in Microbiology, 2021)
Finafloxacin is a novel fluoroquinolone with optimal antibacterial activity in low pH environments, therefore offering a therapeutic advantage over some traditional antibiotics, in treating bacterial infections associated with acidic foci. Coxiella burnetii, the causative agent of Q fever, is a bacterium which resides and replicates in acidic intracellular parasitic vacuoles. The efficacy of finafloxacin was evaluated in vivo using the A/J mouse model of inhalational Q fever and was compared to doxycycline, the standard treatment for this infection and ciprofloxacin, a comparator fluoroquinolone. Finafloxacin reduced the severity of the clinical signs of infection and weight loss associated with Q fever, but did not reduce the level of bacterial colonisation in tissues compared to doxycycline or ciprofloxacin. However, histopathological analysis suggested that treatment with finafloxacin reduced tissue damage associated with C. burnetii infection. In addition, we report for the first time, the use of viable counts on axenic media to evaluate antibiotic efficacy in vivo.